2015
DOI: 10.4172/2157-7412.1000275
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Interaction between the Alpha1-Adrenoceptors (α1-AR) and Transient Receptor Potential (TRP) Triggers a Proliferative Cell Signal in Prostate Cancer Cell Lines

Abstract: Calcium (Ca2+) increases the proliferation of human advanced prostate cancer (PCa) cells but the ion channels involved are unknown. Santoni and Quaglia groups investigated the correlation between alpha1D-adrenergic receptor (α1D-AR) and the transient receptor potential vanilloid type 1 (TRPV1) ion channel expression in PCa cells. The α1D-AR and TRPV1 mRNAs are increased in PCa compared to BPH. α1D-AR and TRPV1 are co-expressed in PCa cells. Norepinephrine (NE) induced α1D-AR-and TRPV1-dependent protons release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Functional TRPC6 channels are found to be overexpressed in prostate, stomach, breast cancers, as well as neuroglia, as compared to the low or undetectable levels in the corresponding normal tissues. Recent studies have demonstrated [Ca 2+ ] c rise mediated via activation of α1-adrenoceptors in normal mesangial cells and prostate cancer cells, which elicits a proliferative signal, implicating the control in cell proliferation (Santoni et al, 2015). In prostate cancer mouse model of knock-In mouse adenocarcinoma prostate (KIMAP), dietary supplement of high Ca 2+ accelerated the progression of prostate tumors in a manner that involves increasing the expression of calcium sensing receptor and TRPC6, an effect that was attenuated through dietary supplement of Vitamin D3.…”
Section: Modulators For Cancers-trpc Channels Have Been Implicated Inmentioning
confidence: 99%
“…Functional TRPC6 channels are found to be overexpressed in prostate, stomach, breast cancers, as well as neuroglia, as compared to the low or undetectable levels in the corresponding normal tissues. Recent studies have demonstrated [Ca 2+ ] c rise mediated via activation of α1-adrenoceptors in normal mesangial cells and prostate cancer cells, which elicits a proliferative signal, implicating the control in cell proliferation (Santoni et al, 2015). In prostate cancer mouse model of knock-In mouse adenocarcinoma prostate (KIMAP), dietary supplement of high Ca 2+ accelerated the progression of prostate tumors in a manner that involves increasing the expression of calcium sensing receptor and TRPC6, an effect that was attenuated through dietary supplement of Vitamin D3.…”
Section: Modulators For Cancers-trpc Channels Have Been Implicated Inmentioning
confidence: 99%